Strategi Pemasaran Film Lokal Sidoarjo: Model Pemasaran Dan Distribusi Film Lokal - Fikri, M. Andi; Istiqomah, Istiqomah; Susilo, Joko (Universitas Nahdlatul Ulama Blitar, 2025)
This study explores the marketing communication and distribution strategies of local films in Sidoarjo through a case study approach involving three active community-based film groups. The objective is to identify the distribution channels utilized, assess the effectiveness of promotional strategies employed, and evaluate the potential for community driven local films to develop independently and sustainably. The research applies a qualitative descriptive method, utilizing observation, in-depth interviews, and document analysis of the film communities’ activities. Findings indicate the use of five primary distribution channels: local film screenings, film festivals, roadshows, alternative screenings, social media, and digital platforms such as Digital TV. Among these, film festivals and alternative screenings emerged as the most dominant strategies due to their wider audience reach and their ability to foster public appreciation of local cinema. Furthermore, elements of the marketing mix such as ticket pricing, digital promotional strategies, visual design, and audience segmentation play a crucial role in strengthening the market positioning of these films. This research demonstrates that community-based local films in Sidoarjo possess the potential to grow independently and sustainably through alternative distribution and digital-based marketing efforts.